Aerosol therapy through high flow nasal cannula in pediatric patients. (2nd December 2017) - Al-Subu, Awni M.; Hagen, Scott; Eldridge, Marlowe; Boriosi, Juan
ABSTRACT: Introduction : High flow nasal cannula (HFNC) is increasingly used in pediatric patients suffering from respiratory failure. In some disease processes, patients may also benefit from aerosol therapy. Therefore, the use of HFNC to deliver aerosolized medications is a convenient and attractive option. Areas covered : This review aims to appraise available evidence concerning the efficiency of aerosol nebulized therapy delivery using HFNC in pediatric patients. Expert commentary : Delivery of aerosol particles is a very complex process and depends on the use of oxygen vs. heliox, nebulizer type and position within the HFNC circuit, patient's breathing effort and pattern, and more importantly cannula size and flow rates. Current in vitro evidence suggests the amount of aerosol delivery is likely to be very low at high flows. Clinical studies are limited in pediatric patients and given the limited clinical data, it is not possible to make recommendations for or against aerosol delivery through HFNC for pediatric patients.